Thirty seconds chair stand performance is associated with six-minute walk test among postmenopausal women: inference from a cross-sectional study among women from India - Hina Vaish; Digvijay Sharma (PAGEPress Publications, 2024)
Menopause is an inevitable yet normal biological process in a woman's life. The menopausal process has been associated with a decline in muscle strength and functional capacity. Thus, the present study aimed to study the association of the 30-Second Chair Stand Test (30s CST) with the 6-Minute Walk Test (6MWT) among postmenopausal women. Thirty-five postmenopausal women aged 40-55 years were included in this cross-sectional study by purposive sampling method. After initial screening and assessment 30s CST and 6MWT were recorded as per standardised guidelines. The mean and Standard Deviation (SD) for all continuous variables was calculated. Correlations were estimated using Pearson's coefficient of correlation. A two-tailed p-value <0.05 was considered statistically significant. There exists a significant positive association of 30s CST values with 6MWD among postmenopausal women. Also, the Rate of Perceived Exertion (RPE) scores after the 6MWT were found to be significantly correlated with RPE scores after 30s CST.  In conclusion, there exists a significant positive correlation of 30s CST with 6MWT among postmenopausal women. The 30s CST could be used as an economical and quick physical function assessment measure among postmenopausal women in low-resource settings.